Organoleptic Perspective of Coffee Skin Eco-enzyme as a Zero Waste Alternative in Plantation Areas - Aditya, Bagas Aditya; Astuti, Andari Puji; Anggianti, Ratna (Newinera Publisher, 2024)
Coffee was a high-value plantation commodity in Indonesia, contributing significantly to farmers' income and the national economy. However, increased coffee production also generated coffee skin waste that was often discarded, creating challenges in organic waste management. This study aimed to process coffee skin waste into eco-enzyme through fermentation process, which could be utilised as organic fertiliser and natural cleaner. For four months, organoleptic observations were made on the eco-enzyme produced, including, colour, pH, volume, and texture. Results showed that the colour of the solution transitioned from light brown to dark brown. pH decreased from 7 to 4 as microbial activity increased. The volume of the solution decreased from 500 mL to 240 mL due to gas release during fermentation. These findings suggested that processing coffee skin waste not only reduced environmental pollution but also increased the economic value of coffee industry by-products. This study provided insight into the potential for sustainable utilisation of coffee waste and supported environmentally friendly agricultural practices.